Livestock and water interactions in mixed crop-livestock farming systems of Sub-Saharan Africa: interventions for improved productivity - Descheemaeker, Katrien K.; Amede, Tilahun; Haileslassie, Amare (International Water Management Institute, 2009)
Focusing on mixed crop-livestock farming systems of Sub-Saharan Africa, this review brings together the available knowledge in the various components of the livestock and water sectors. Through an analysis of livestock-water interactions, promising strategies and interventions to improve Livestock Water Productivity are proposed. In the biophysical domain, the numerous interventions relate to feed, water and animal management. These are interlinked with interventions in the socio-political-economic domain. The paper identifies critical research and development gaps in terms of methodologies for quantifying water productivity and integrating different scales, and also in terms of institutions and policies.